The Macular Choroidal Thickness in Danish Children with Myopia After Two-Year Low-Dose Atropine and One-Year Wash-Out: A Placebo-Controlled, Randomized Clinical Trial - Niklas C. Hansen; Anders Hvid-Hansen; Toke Bek; Flemming Møller; Nina Jacobsen; Line Kessel (Ophthalmology and Therapy)
Abstract Introduction Our aim in this work was to investigate the macular choroidal thickness (ChT) changes in 6–12-year-old Danish children with myopia during 2 years of low-dose atropine treatment and 1-year wash-out vs. placebo in an investigator-initiated, placebo-controlled, double-blind randomized clinical trial. Methods Ninety-seven participants were randomized to either 0.01% for 2 years, 0.1% loading dose for 6 months followed by 0.01% for 18 months, or placebo, then a 1-year wash-out. The primary outcome was ChT in the sub-foveal and inner and outer superior, nasal, inferior, and temporal sectors. The secondary outcome was axial length (AL). Outcomes were measured at baseline and 6, 12, 24, and 36 months. One-way analysis of variance was used to detect baseline ChT differences between AL-stratified groups (< 24 mm, 24–25 mm, or > 25 mm). To determine the longitudinal changes in ChT and its effect on AL, all eyes were included in linear mixed modeling with individual eyes nested in the study ID as a random effect. Results Longer eyes had significantly thinner ChT in all choroidal sectors (adj-P < 0.01) at baseline. There was no statistically significant change in any ChT sector after 3 years in the placebo group. Sub-foveal and nasal ChT in the 0.1% loading dose and 0.01% group were not significantly different from placebo after 2-year treatment. In the placebo group, a 1-mm increase in AL was significantly associated with a 47-µm thinner nasal ChT after 3 years (95% confidence interval (CI): – 55; – 38, adj-P < 0.001). A 10-µm thicker nasal choroid at baseline was associated with 0.13 mm (95% CI: 0.009; 0.017, adj-P < 0.001) less 3-year axial elongation. Conclusions The ChT in Danish children with myopia remained stable over the 3-year follow-up. A thinner choroid at myopia onset might predispose to increased axial elongation. Treatment with 0.01% atropine did not change the ChT. We speculate that low-dose atropine does not primarily reduce myopia progression via a choroidal mechanism. Trial Registration ClinicalTrials.gov identifier, NCT03911271.